ACESSIBILIDADE AO DISPOSITIVO INTRAUTERINO (DIU) NA ATENÇÃO PRIMÁRIA À SAÚDE - KÁTIA MELO CAVALARI (2022)
The copper intrauterine device (IUD) is a reversible contraceptive method most used worldwide, it is offered by the Unified Health System (SUS), being totally safe and highly effective, with low rates related to its failure, but still underutilized by the Brazilian population. This restriction on their membership may restrict the full exercise of sexual and reproductive rights by Brazilian women. Therefore, the objective of this study was to know the conditions of women's access to the IUD in Primary Care in the city of Campo Grande - MS. For this, a qualitative study was carried out, which involved conducting individualized interviews based on semi-structured scripts. As a data analysis technique, the Consolidated Framework for Implementation Research (CFIR) was used as a guide to establish the evaluation constructs. The domains of the internal scenario were used; external scenario and characteristics of CFIR individuals for the results analysis. Interviews were carried out with four groups of 10 participants each: women users of the SUS who seek care for the insertion of the IUD, women users of the SUS who inserted the IUD, primary health care professionals who do not and who insert the device. The interviews were guided by a previously established script, based on triggering questions about the flow, access and availability of the IUD. 40 interviews were analyzed, from which the reports were organized, and categories were defined. The interviews were audio recorded, transcribed, read, and reread. After this step, the content analysis was carried out following its steps: floating reading, pre-analysis, and thematic categorization. It is noteworthy from the results found that despite some facilities being recognized, there are still many limitations and barriers of knowledge, organizational and operational that make it difficult for women to access the insertion of the intrauterine device by users of the health units to which they are attached.